(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
An in-depth analytical study of Taslima Nasrin’s Lajja (Shame) reveals that religious fanaticism plays a very derogatory role in dividing human beings on the basis of religion and inciting them to destroy their lives. She depicts a Hindu family which believed in communist ideology and cherished a number of hopes for security, liberty and equality in East Pakistan. Suranjan, the mouthpiece of Nasrin and the incarnation of Jimmy Porter, is a leftist intellectual; dreaming of humanity for Hindu Minority in Bangladesh. But he found that Hindus’ lives were badly impacted by the events between 1947 to 1992 during which social taboos and religion became the basis of politics and the country became an Islamic state marginalizing the minorities mostly Hindus. He gathered a number of persecutions in his heart and mind; and never retaliated till the abduction of his real sister. This incident brought out his hidden anger and hatred for Muslim Majority and he retaliated against them. He joined the Hindu organization to demolish the mosques and raped a Muslim whore very brutally to take revenge of his sister’s abduction. His family suffered such irreparable losses that it was forced to leave Bangladesh for India. Nasrin dares to condemn the Muslim fanatics and makes a universal appeal to human beings to live with love, peace and harmony thwarting political manipulations in the name of religion.